The Effect of Chance Variation on Revenue and Cost Estimations for Breakeven Analysis. - Liao, Mawsen (The Accounting Review, 1976)
This article focuses on the effect of chance variation on revenue and cost estimations for break-even analysis. Break-even analysis consists essentially of examining the relationship between revenues and costs. The regression models use historical data to predict future revenue-volume and cost-volume relationships. The model, suggestively, is good if the environment does not change. The break-even analysis based on estimated revenue and cost functions, therefore, is subject to chance variation. The purposes of this article is twofold: first, to demonstrate the determination of the chance variation in estimated revenue and cost functions, and second, to illustrate how the chance variation associated with revenue and cost estimations affect the results of a break-even analysis. According to the author, regression analysis can be a helpful tool for predictions of future revenue and cost if fundamental assumptions in the model are satisfied. The most important assumption of regression analysis is that the historical relationship between the dependent variable and independent variable will persist. Therefore, one of the problems of using regression analysis is that the future relationships may not coincide with the relationships indicated by mathematical equations derived from historical data.